Our Experience in Database Entry in Ear Surgery - Shrestha, B.L. (Kathmandu University Medical Journal, 2020)
Otological database is must for every otological surgeon. The surgeons who do not have their own surgical database have difficult in convincing the patients about the outcome of procedure. Looking at the literature review about the concerned surgery does not reflect the success rate of the surgeon who is performing the surgery. So it is very important for every surgeon to have their own data base. The database helps surgeon to improve their skills and compare their own surgical results within and with other literatures. This helps the surgeon to convince patients regarding success and failure rates of their surgery. Not only that, but it also helps to perform prospective research work.